A cross-sectional study of evidence-based practice and its determinants among healthcare professionals in Northwest Ethiopia - Melkamu, Yideg; Asemahagn, Mulusew Andualem; Walle, Ayinengida Adamu; Tsega, Yawkal (Frontiers in Medicine, 2024)
Background Evidence-based practice (EBP) is the integration of current best evidence with clinical expertise by considering patient preferences and values. Evidence based practice has not been well studied in Ethiopia. Therefore, this study aimed to assess EBP and its determinants among health professionals working at primary public hospitals in the Central Gondar zone, Northwest Ethiopia. Methods A facility-based cross-sectional study was conducted on 422 health professionals. A simple random sampling technique was used to select the study participants. The data were entered into EpiData version 4.6 and exported to SPSS version 25 for analysis. The descriptive, bivariable, and multivariable logistic regression analysis were conducted. Adjusted Odds Ratio (AOR) with 95% confidence intervals and p-value <0.05 were used to assess association of explanatory variables with EBP and declare statistical significance, respectively. Result About 44.1% (95%CI: 39, 50%) of healthcare professionals had good evidence-based practice. Educational status (AOR: 3.05, CI: 1.07–8.66), spare time (AOR: 1.90, CI: 1.09, 3.31), good knowledge (AOR: 7.95, CI: 4.83, 13.08), good skill (AOR: 2.39: CI: 1.27, 4.53), training (AOR: 2.13, CI: 1.26, 3.58), and internet access (AOR = 2.02: 95% CI: 1.25–3.27) were found to be significant predictors of evidence-based practice. Conclusion This study revealed that EBP was low compared to national standards. Moreover, having good knowledge and skill about evidence-based practice, being trained, having spare time and internet access and upgrading educational status of health care professionals would enhance good evidence-based practice.